2020
DOI: 10.3389/fendo.2019.00915
|View full text |Cite
|
Sign up to set email alerts
|

Role of OCT4 in the Regulation of FSH-Induced Granulosa Cells Growth in Female Mice

Abstract: As a member of the POU (Pit-Oct-Unc) transcription factor family, OCT4 (Octamer-binding transcription factor 4) is associated with the cellular proliferative. However, the roles of OCT4 in regulating the transition from preantral follicle to early antral follicle are still remains unclear. To evaluate the effect of OCT4 on cellular development in ovary, mice were injected with eCG in vivo or granulosa cells were co-cultured with FSH in vitro. The results showed that eCG up-regulated ovarian OCT4 expression. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Recently, a study in mice showed that FSH can be involved in ovarian cell development through the regulation of OCT4 expression in granulosa cells at the preantral to early antral transition stage of follicles via the glycogen synthase kinase (GSK)-3β/β-catenin pathway, and this response was found to be mediated by the phosphoinositide 3-kinases/serine/threonine kinase (PI3K/Akt) signaling pathway [ 172 ]. In many species, GCs from preantral (at the secondary follicle stage) and antral follicles at different stages of follicular growth were shown to express FSHR [ 126 , 127 , 128 ].…”
Section: Influence Of Fsh On Germ Cellsmentioning
confidence: 99%
“…Recently, a study in mice showed that FSH can be involved in ovarian cell development through the regulation of OCT4 expression in granulosa cells at the preantral to early antral transition stage of follicles via the glycogen synthase kinase (GSK)-3β/β-catenin pathway, and this response was found to be mediated by the phosphoinositide 3-kinases/serine/threonine kinase (PI3K/Akt) signaling pathway [ 172 ]. In many species, GCs from preantral (at the secondary follicle stage) and antral follicles at different stages of follicular growth were shown to express FSHR [ 126 , 127 , 128 ].…”
Section: Influence Of Fsh On Germ Cellsmentioning
confidence: 99%
“…In line with the predicted results of network pharmacology, we detected a remarkably decreased level of GSK3β (Tyr216) and increased level GSK3β (Ser9) of in KXS-treated group, which indicated a significant inhibition of GSK3β activation. The best studied mechanism by which GSK3β is regulated is Akt-dependent serine phosphorylation [ 51 ]. AKT phosphorylates GSK3β at the S9 residue, which inactivates GSK3β [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this study still has some limitations including our use of KGN cells as a TRIB3 gene knockdown model. Although the KGN cell line is more likely to be closer to granulosa cells in normal physiological conditions than other human cell lines [39], additional studies are warranted because this model does not completely replicate the physiological environment of the human body. Furthermore, the TRIB3 effect on the granulosa cells or even on the folliculogenesis in conditional TRIB3 gene knockout mouse model also needs further study.…”
Section: Discussionmentioning
confidence: 99%